The effects of material formulation and manufacturing process on mechanical and thermal properties of epoxy/clay nanocomposites - Salam, H.; Dong, Yu; Davies, Ian; Pramanik, Alokesh (Springer, 2016)
A holistic study was conducted to investigate the combined effect of three different pre-mixing processes, namely mechanical mixing, ultrasonication and centrifugation, on mechanical and thermal properties of epoxy/clay nanocomposites reinforced with different platelet-like montmorillonite (MMT) clays (Cloisite Na+, Cloisite 10A, Cloisite 15 or Cloisite 93A) at clay contents of 3–10 wt%. Furthermore, the effect of combined pre-mixing processes and material formulation on clay dispersion and corresponding material properties of resulting composites was investigated using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), flexural and Charpy impact tests, Rockwell hardness tests and differential scanning calorimetry (DSC). A high level of clay agglomeration and partially intercalated/exfoliated clay structures were observed regardless of clay type and content. Epoxy/clay nanocomposites demonstrate an overall noticeable improvement of up to 10 % in the glass transition temperature (Tg) compared to that of neat epoxy, which is interpreted by the inclusion of MMT clays acting as rigid fillers to restrict the chain mobility of epoxy matrices. The impact strength of epoxy/clay nanocomposites was also found to increase by up to 24 % with the addition of 3 wt% Cloisite Na+ clays. However, their flexural strength and hardness diminished when compared to those of neat epoxy, arising from several effects including clay agglomeration, widely distributed microvoids and microcracks as well as weak interfacial bonding between clay particles and epoxy matrices, as confirmed from TEM and SEM results. Overall, it is suggested that an improved technique should be used for the combination of pre-mixing processes in order to achieve the optimal manufacturing condition of uniform clay dispersion and minimal void contents.